PECULIARITIES OF SELECTION OF THE ELECTROMAGNETIC DISTRIBUTION MODEL RADIATION INSIDE THE ROOM - Бахтіяров, Денис Ілшатович (Science-based technologies, 2019)
This article deals with the distribution of radio waves inside buildings and spaces to further build a system of defense of information from side-by-side electromagnetic radiation and intrusion. The presence of inside the building of walls, partions, furniture, electronic equipment, people and other objects creates a complex distribution of radio waves. Thus, the conditions for radio waves in the interior vary significantly from the distribution of radio waves in free space. The purpose of analyzing radio waves is to calculate the range of electromagnetic radiation and to determine the real characteristics of the signal. The classical approach to the settlement of the electromagnetic field is to calculate the tension of the field in a single isotropic space based on the laws of reflection, diffraction, and scattering. However, because of the special conditions in the room, the possibility of directly applying the method is excluded. Technical means of information processing, which in the process of carrying out its processing, storage and transmitting make it possible to generate electromagnetic radiation, which is by bit, or parasitic. Thus, the nonlinear processes in the equipment units of machinery are generated and emitted into the surrounding space by the side of the electromagnetic radiation and the radiation that can be sufficient for the radio to be acceptable at a certain distance from mechanical means. Therefore, it becomes urgent to determine the optimal model for the description of threats through the channel of leakage of electromagnetic radiation and intrusion, as well as the size of the controlled area, which controls the presence of unauthorized persons and unauthorized stay in the facility, and the ability to use intelligence equipment, because in this the area is likely to intercept information.